Impact of Combined Administration of Cryopreserved Mesenchimal Stem Cells and Neural Cell Aggregates on Recovery of Motor Activity in Rats with Intracerebral Hemorrhage - Zolotko, Kyrylo; Sukach, Olexandr; Kompaniets, Antonina; Piriatinska, Nataliia (Problems of Cryobiology and Cryomedicine, 2020)
The effect of implantation of cryopreserved neural cells (NCs) within the neural cells aggregates (NCAs) together with mesenchymal stem cells (MSCs) on the recovery of rat behavioural functions and motor activity after intracerebral hemorrhage (ICH) has been studied. The ICH was simulated by stereotactic injection of collagenase into rat striatum, resulted in loss of sensitivity on the affected side, disorder in motor activity and significant asymmetry of sensory-motor deficits in animals. The cryopreserved NCs (1.5 × 106 cells) within the aggregates and cryopreserved MSCs (1.0 × 106 cells) were implanted into the lateral ventricles of rat brain. A significant recovery of tactile sensitivity, improvement in the skilled tasks performance, as well as a decrease in the asymmetry of sensory-motor deficits in the ICH rats after implantation of cryopreserved NCAs, as well as the combination of the latter with MSCs, have been experimentally established. The implantation of cryopreserved MSCs together with NCAs led to an earlier improvement in behavioural-motor functions in rats with ICH as compared to the animals received the NCAs only. Probl Cryobiol Cryomed 2020; 30(2): 169–177